Procedural Justice as Fairness in Ghana - Amuzu, T. E. (University of Ghana, 2025)
This thesis seeks to develop an appropriate theoretical and normative framework to assess the fairness of the application of procedural rules in Ghana. It posits that, to be fair, the application of the rules must be from the original position as a preferred standpoint, be de-colonised and aim at achieving relationality. This is because the combined effect of article 19(13) of the 1992 Constitution of Ghana and Order 1, rule 1(2) and Order 81, rule 1(1) of the High Court (Civil Procedure) Rules, 2004 (CI 47) creates a certain normative framework of fairness which encourages expedition and eschews technicalities. However, these norms are not routinely relied upon in the application of procedural rules, leading to setting aside cases which are deemed to have fundamentally offended the rules. The insistence of courts to strictly apply procedural rules often deny litigants the opportunity to have their substantive concerns addressed. This reflects the situation which existed in 15th century England where every claim had to comply with a specific writ or it failed. The writ system was influenced by a philosophy of strict compliance with form, which was imported into Ghana through colonialism. Through a qualitative doctrinal legal research, I explore an appropriate framework for the application of procedural rules. I rely on John Rawls’s justice as fairness theory built on the ‘original position’, where participants in a thought experiment, make choices of principles from ‘behind a veil of ignorance’ to govern them. This veil deprives them of their peculiar identities which pre-dispose them to bias choices, making their choices fair, and therefore just. The choices at the original position may reflect colonial influences. Where this is the case, divesting the people of these tendencies (de colonisation) is crucial. Further, Rawls’s justice as fairness theory has been criticised as based on the individual as the moral agent, hence may not adequately take account of African ideas of ‘relationality.’ To resolve this potential tension, this thesis borrows Metz’s afro-communitarian relational theory of justice to moderate decisions at the original position to create a Modified Afro-Communitarian Relational Theory of Justice (MART Justice). When MART Justice guides the application of procedural rules, the result is that the rules will go through a fundamental shift and be contextually more just, hence fair. To demonstrate the application of MART Justice, this thesis uses three cases decided by the Supreme Court of Ghana on originating processes.
PhD. Law
Keywords: procedural rules; fairness; Ghana